Assessment of agronomic performance of PPV resistant ‘HoneySweet' transgenic plum in ecological conditions of the Northern Romania - L.A. Zagrai; I. Zagrai; R. Scorza; M. Ravelonandro; C. Dardick; G. Guzu (Romanian Journal of Horticulture, 2021)
‘HoneySweet’ is an RNAi based genetically engineered plum resistant to Plum pox virus (PPV). Field trials in different European PPV endemic countries clearly demonstrated that ‘HoneySweet’ plum shows a highly effective and durable resistance to PPV infection. No safety concerns were found by regulatory authorities in the U.S. Expanded studies to assess the agronomic performance of ‘HoneySweet’ plum were performed under PPV endemic and ecological conditions of Northern Romania. An experimental plot including transgenic plum, ‘HoneySweet’, and two conventional plum cultivars, ‘Reine Claude d’Althan’ and ‘Stanley’, was established in spring of 2013. Agronomic performance data collected during 2016-2018 revealed a higher yield potential for transgenic ’HoneySweet’ compared to ‘Reine Claude d’Althan’ and a similarity with ’Stanley’. Average fruit weight highlighted the superior attributes of transgenic ‘HoneySweet’ compared with the two conventional plum cultivars. ‘HoneySweet’ transgenic plum fruits were larger, had lower stone/fruit ratio, and more optimal shape and colour relative to ‘Reine Claude d’Althan’ and ‘Stanley’, and a high level of resistance to PPV infection. These data and observations revealed that ‘HoneySweet’ transgenic plum has good productivity and market potential and is well adapted to PPV endemic and ecological conditions of the Northern Romania.